2021
DOI: 10.3390/atmos12101283
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Trend of NO2, SO2 and CO over East Africa from 2005 to 2020

Abstract: The atmospheric chemistry constituents of nitrogen dioxide (NO2), sulphur dioxide (SO2) and carbon monoxide (CO) are associated with air pollution and climate change. In sub-Saharan Africa, a lack of sufficient ground-based and aircraft observations has, for a long time, limited the study of these species. This study thus utilized satellite observations as an alternative source of data to study the abundance of these species over the East African region. The instruments used included the Ozone Monitoring Instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These compounds also have short atmospheric lifetimes, realistically, days to months. SO2 is in the atmosphere for two days, while for NO2, the time is longer at 1 to 10 days, and CO has a maximum residence time of thirty to ninety days [16]. Although at the three sampling points, it was found that CO exposure was still below the threshold (<10000 µg/Nm 3 ) because of its strong bond with the hemoglobin molecule, carboxyhemoglobin was formed.…”
Section: Air Quality As a Results Of Exposed Coal Dustmentioning
confidence: 89%
“…These compounds also have short atmospheric lifetimes, realistically, days to months. SO2 is in the atmosphere for two days, while for NO2, the time is longer at 1 to 10 days, and CO has a maximum residence time of thirty to ninety days [16]. Although at the three sampling points, it was found that CO exposure was still below the threshold (<10000 µg/Nm 3 ) because of its strong bond with the hemoglobin molecule, carboxyhemoglobin was formed.…”
Section: Air Quality As a Results Of Exposed Coal Dustmentioning
confidence: 89%
“…It has been previously used to examine the effect of wildfires on O 3 , compliance with NAAQS, and to smooth the effects of local meteorology and short-term changes in local emissions [24,25]. The annual trend was computed using the de-seasonalized monthly 8-h max O 3 concentrations by applying the non-parametric sequential Mann-Kendall test at a confidence level of 95% [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the model may not be valid since the concentrations are out of the given range. However, for future biogas estimates, we will compare with other models to develop our own model considering the climatic conditions, the characteristics of the waste and concentrations of the gases typical of the sector where the landfill is located [16,32,53,54]. Hence, in the results of works performed in 2011, the potential for electrical production of biogas, generated in the Pichacay landfill, calculated through theoretical models conducted by the (EPA), assuming a concentration of 50% CH 4 and 50% CO 2 starting in 2009, it has been estimated that it will reach a higher point of biogas generation in 2019, with 1152 m 3 /h with a maximum capacity of 1.90 MW.…”
Section: Pichacay and Las Iguanas Landfill Gas Analysismentioning
confidence: 99%